Translational initiation in Leishmania tarentolae and Phytomonas serpens (Kinetoplastida) is strongly influenced by pre-ATG triplet and its 5' sequence context - Lukes, Julius; Paris, Zdenek; Regmi, Sandesh; Breitling, Reinhard; Mureev, Sergey; Kushnir, Susanna; Pyatkov, Konstantin; Jirků, Milan; Alexandrov, Kirill A (Molecular and biochemical parasitology, 2006)
To investigate the influence of sequence context of translation initiation codon on translation efficiency in Kinetoplastida, we constructed a library of expression plasmids randomized in the three nucleotides prefacing ATG of a reporter gene encoding enhanced green fluorescent protein (EGFP). All 64 possible combinations of pre-ATG triplets were individually stably integrated into the rDNA locus of Leishmania tarentolae and the resulting cell lines were assessed for EGFP expression. The expression levels were quantified directly by measuring the fluorescence of EGFP protein in living cells and confirmed by Western blotting. We observed a strong influence of the pre-ATG triplet on the level of protein expression over a 20-fold range. To understand the degree of evolutionary conservation of the observed effect, we transformed Phytomonas serpens, a trypanosomatid parasite of plants, with a subset of the constructs. The pattern of translational efficiency mediated by individual pre-ATG triplets in this species was similar to that observed in L. tarentolae. However, the pattern of translational efficiency of two other proteins (red fluorescent protein and tetracycline repressor) containing selected pre-ATG triplets did not correlate with either EGFP or each other. Thus, we conclude that a conserved mechanism of translation initiation site selection exists in kinetoplastids that is strongly influenced not only by the pre-ATG sequences but also by the coding region of the gene.
Keywords: zelené fluorescenční proteiny; červený fluorescenční protein; regulace genové exprese; 5' nepřekládaná oblast; kodon iniciační; Codon, Initiator; Green Fluorescent Proteins; rezistence na tetracyklin; zvířata; reportérové geny; transfekce; proteosyntéza; Gene Expression Regulation; Red Fluorescent Protein; 5' Untranslated Regions; Genes, Reporter; Trypanosomatina; Luminescent Proteins; Transfection; Leishmania; Animals; luminescentní proteiny; Tetracycline Resistance; Protein Biosynthesis